Pengolahan Limbah Serat Fiber sebagai Substitusi Material Pengisi Media Tanam Organik di Mitra WBS Fiberglass Poncokusumo - Asrori, Muhammad Roy; Santoso, Aman; Sumari, Sumari; Prakasa, Yana Fajar; Mahmudah, Siti Nur (LPkM Universitas Bakrie, 2023)
Micro-enterprises in the community still need a helping hand in the form of a service program from the campus. It is known that the micro-enterprise community belongs to the lower middle class, so there is still a lack of interest in seeking information/literacy and this results in the absence of business development in the future in a better direction. In Karanganyar Village, Poncokusumo, Malang, a fiber business was found in the manufacture of tools made of plastic, this business has been running for 3 years and there is still no high enough development. In addition, another problem is the problem of fiber waste that has not been utilized at all. There was no processing or conversion into useful and economically valuable materials. The solution offered is the manufacture of organic pots/growing media. The method of implementing this service used three stages, namely preparation, implementation, and reporting. The data collected in the form of documentation, observation, and the results of filling out the respondent's questionnaire which was then analyzed descriptively qualitatively. The results of the service showed that organic growing media from fiberglass can be applied and attract partners' interest. Knowledge of occupational health and safety has enthusiastically educated partners. The results of the partner satisfaction questionnaire showed that this service activity has a very satisfied response category of 65.7% and a satisfied response of 34.3%. So, WBS fiberglass partners have received, supported, appreciated, and followed this service well.